Cultural Awareness of Indonesia in the Eyes of the World: An Analysis of “That Evan Guy” Vloggers’ Perception of Indonesia’s Cultural Strength and Modernity - Mahmuliana, Ika Firdausi Aini (Fast in Humanities, 2026)
This study examines how Indonesian culture and modernity are discursively constructed in global digital space through the YouTube travel narrative of a foreign vlogger, That Evan Guy. The study departs from the observation that external digital representations of Indonesia often diverge from dominant domestic narratives, particularly regarding infrastructure quality, cleanliness, and cultural coexistence with modernity. These differences indicate a form of perceptual discordance that warrants critical examination at the level of discourse rather than opinion. Employing a qualitative approach grounded in Critical Discourse Analysis, the study analyzes selected excerpts from a verbatim transcript of a YouTube video documenting railway stations and high-speed train services in Indonesia. Data were collected through documentation, transcription, and non-participant content observation, then analyzed using thematic coding and discourse analytical procedures to identify evaluative framing, positioning, comparison, presupposition, and omission within the narrative. The findings show that Indonesian modernity is constructed through systematically positive evaluative language, emphasis on accessibility and ordinariness, and contrastive comparison with Western contexts. Cleanliness and infrastructure quality function as key discursive signifiers that challenge dominant global stereotypes associated with developing countries. The analysis further reveals that perceptual discordance emerges not from factual disagreement, but from competing discursive regimes that assign value and legitimacy differently to culture and development. The study concludes that foreign vlogger narratives operate as influential discursive sites where national culture and modernity are symbolically negotiated outside institutional frameworks.